Ensino de Ciências para anos iniciais: seleção de conteúdos curriculares a partir do conceito de tema gerador de Paulo Freire - Cristiane Mendes da Silva Dantas (2018)
The construction of a curricular proposal is one of the major tension points between those involved in the research and management in the educational field and among the teachers themselves, who are responsible for implementing the curriculum in schools. Driven by the discussions that have been occurring in the current educational scenario, this research aims to present a proposal to select curriculum content based on Paulo Freire's conception of education, more specifically in the concept of theme generator. The research also supports the work of Demetrius Delizoicov and Marta Maria Pernambuco, which offer theoretical support for the implementation of the ideas of Paulo Freire in science teaching. The research was developed with a second-year class of elementary school, in a public school of Belo Horizonte, Brasil. The main objective of the research is to seek new paths to the selection of content for science teaching and, from that experience, to elaborate a didactic material directed to education professionals, which canbe used in schools as support for the discussions about curricular construction. The expectation is that teachers become interested in the thematic, and feel encouraged to break traditionalist practices in education that often do not contemplate the desires and needs of the students or the local community.